KOMPARASI PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE TGT (TEAM GAME TOURNAMENT) DENGAN NHT (NUMBER HEAD TOGETHER) TERHADAP PRESTASI BELAJAR MATEMATIKA POKOK BAHASAN BILANGAN PECAHAN PADA SISWA KELAS IV SDN SADAH KABUPATEN LOMBOK TENGAH NTB - Moh Erwin Budiana (LPPM Institut Pendidikan Nusantara Global, 2020)
This study aims to compare the effectiveness of the cooperative learning model type TGT and cooperative learning model NHT in the Linear Program material. This type of research is quasi-experimental research (Quasi expeiment). he population in this study were all students of class IV of the SDN Liwung School and the sample consisted of two classes, namely the experimental group I, namely the TGT type cooperative model. and experimental group II, which was taught using a cooperative model type NHT which was taken by using simple random sampling technique (simple random sampling). The results of the study show that the application of the TGT cooperative learning model in the category very effective with student learning outcomes in the high learners in learning activities that are in the active category, and the response students of the device in learning are in the positive category.